FETAL ANATOMICAL VARIABILITY OF THE ULNAR AND RADIAL ARTERY SYSTEM - О. Коваль; Т. Хмара; І. Заморський; М. Кривчанська; О. Гарвасюк (Неонатологія, хірургія та перинатальна медицина, 2024)
Variability in the topography of the arteries of the upper extremity is associated with fetal development. Determination of individual anatomical variants of the upper extremity blood supply at diff erent stages of ontogeny, especially in human fetuses, is of great practical importance in vascular surgery. Aim of the study. To study the individual anatomical variability of the ulnar and radial arteries in human fetuses of diff erent ages. Material and methods. The study of variants of the topography of the branches of the radial and ulnar arteries, the peculiarities of the formation of the superfi cial palmar arterial arch was carried out on 46 preparations of the upper extremities of 23 human fetuses 81. 0-375, 0 mm parieto- coccygeal length using macromicroscopic dissection, vascular injection and morphometry without external signs of anatomical abnormalities or congenital malformations of skeletal, fascial- muscular and vascular- nerve structures of the upper extremities. Results and discussion. Our study demonstrated fetal anatomical variability and bilateral asymmetry of the right and left upper extremity arteries in human fetuses. Thus, in a fetus with a PCL of 210.0 mm, the right brachiocephalic artery was found to originate from the right axillary artery. It should be noted that the initial portion of the right brachiocephalic artery passed anteriorly, not posteriorly, to the median nerve, and at the level of the middle third of the anterior shoulder region, the artery occupied a superfi cial position relative to the median nerve, which is located in the lateral bicuspid groove of the shoulder. The brachiocephalic artery was then directed in an oblique lateral direction to the lateral surface of the forearm. In this fetus, a high origin of the right ulnar artery was found, which originated from the trunk of the brachiocephalic artery in the upper third of the right anterior shoulder region. At the border of the middle and lower thirds of the anterior shoulder region, the ulnar artery crossed the ulnar nerve anteriorly and passed with it in the median biceps groove of the shoulder. 3.0 mm below the beginning of the ulnar artery, the superior circumfl ex ulnar artery bifurcated from the brachiocephalic artery, and in the lower third of the anterior shoulder region, a common trunk bifurcated from the brachiocephalic artery and bifurcated into the middle and inferior circumfl ex ulnar arteries. We found arterial anastomoses between the latter and branches of the ulnar artery. The immediate continuation of the right brachiocephalic artery in the palm was the brachiocephalic artery of the thumb. At the level of the base of the proximal phalanx of the thumb, the brachiocephalic artery branched into three palmar fi nger arteries, which were directed to both edges of the palmar surface of the fi rst fi nger and the radial edge of the palmar surface of the second fi nger. The superfi cial palmar arch was formed by the superfi cial palmar branch of the brachial radial artery, the terminal ulnar artery, and the anterior interosseous artery. Four common palmar arteries originated from the superfi cial palmar arch and were directed to the ulnar edge of the palmar surface of the second fi nger and the palmar surfaces of the adjacent edges of the third through fi fth fi ngers. The left superfi cial palmar arch had an atypical structure located under the palmar aponeurosis at the level of the middle of the metacarpals and formed by the terminal parts of the ulnar and anterior interosseous arteries. Because the radial artery in this fetus was traced to the distal part of the forearm (to the scaphoid bone), we did not fi nd branches of this artery in the palm area, especially the superfi cial palmar branch of the radial artery. The ulnar artery was directed caudally to the palmar region, curving slightly in an arc to the radial side of the hand. From the terminal portion of the ulnar artery, three common palmar fi nger arteries bifurcated, which in turn bifurcated into fi ve palmar fi nger arteries of their own. The latter supplied the ulnar edge of the third fi nger and the palmar areas of the fourth and fi fth fi ngers. The radial edge of the third fi nger and the palmar areas of the II-I fi ngers were supplied by fi ve separate palmar arteries originating from the terminal portion of the anterior interosseous artery. Anastomoses were found between the palmar arteries, mainly in the middle and terminal phalanges. In the area of the palm, numerous muscular branches bifurcated from the anterior interosseous and ulnar arteries, providing blood supply to the palm muscles. Conclusions. In the majority of the studied fetuses (82.61 %) the superfi cial palmar arch was closed, in 17.39 % of the observations it was not closed. In 10.5 % of cases, the superfi cial palmar arch was formed by the trunk of the ulnar artery and the median forearm artery, and in 5.2 % – with the participation of the ulnar and anterior interosseous arteries. The ulnar artery is predominantly involved in the formation of the superfi cial palmar arch. In a fetus with a PCL of 210.0 mm, the right brachiocephalic artery was found, as well as a high origin of the right ulnar artery from it and an atypical branching of other branches. In particular, the superfi cial palmar arch was formed by the superfi cial palmar branch of the brachial radial artery, the terminal ulnar artery, and the anterior interosseous artery, while the left superfi cial palmar arch was formed by the terminal ulnar and anterior interosseous arteries.